(untitled) (مجلة إحالات, 2026)
This research paper aims to uncover the impact of the Corona pandemic (Covid-19) on contemporary Arabic poetry, by revealing the profound impact it has left on the hearts of contemporary poets, by highlighting the negative and positive psychological concerns that they faced, which were the reason for their multiple pens in expressing this phenomenon. Jassim Al-Sahih, Esmat Radwan, Ahmed Mahdi AlHakami, Muhammad Saleh Al-Jazaeri, Nouri Siraj Al-Waeli, Abdulaziz Al-Hammami.